PERSEPSI DAN MINAT MASYARAKAT TERHADAPBUDIDAYA Trigona spp. DI SEKITAR HUTAN LARANGAN ADAT RUMBIO KABUPATEN KAMPAR - Akhmad Rafdi Azhimi; Defri Yoza; M. Mardhiansyah M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
One of the non-timber forest products that have the potential to be developed of honey from  Trigona  spp. which have cultivated in the area of forest by community. Trigona spp. is one of bees without sting. Many  Trigona spp. defend themselves with  biting their enemy. This bees will biting their enemy or burn their enemy  with dissolved chemical alkali. The lack of information and understanding about potential of Trigona spp. Cultivation and utlization arround forbidden forest in Rumbio customary also the unmaximal benefiting by community arround forbidden area. The purpose of this research to understand community interest and perception toward Trigona spp. cultivation arround forbidden forest in rumbio customary. This research has be done in the forbidden forest area, Siboghia, Rumbio Village, Kampar District, Riau Province. The sample thad been  used is purposive sampling.  Respondents that has been selected for this reasearch are 30 peoples from forbidden community. Respondents living passed arround forbidden forest, and had a farm in area, as the main data source of this research. Based on this research, it can be seen that community interest and perception toward Trigona spp. cultivation are good. The respondents not only know about the type and physiology of Trigona spp., but also know the habitats and products of Trigona spp. The knowledge of respondent still not enough. But the interest of respondents to cultivating Trigona spp. Is sufficient. Keywords : public perception, interest, Trigonaspp.